Measuring Violent Conflict in Micro-level Surveys : Current Practices and Methodological Challenges - Brück, Tilman; Justino, Patricia; Verwimp, Philip; Avdeenko, Alexandra; Tedesco, Andrew (Published by Oxford University Press on behalf of the World Bank, 2017)
This paper reviews current practices and common challenges in the measurement of the causes, functioning, and consequences of violent conflict at the micro-level. We review existing conflict- and violence-related survey questionnaires, with a particular focus on the World Bank's Living Standard Measurement Surveys. We discuss methodological challenges associated with empirical work in conflict-affected and fragile areas—such as operationalizing a definition of conflict, using the appropriate units of analysis, deciding on the timing of the survey, dealing with data biases, and conducting surveys in an ethically sound manner under conditions of insecurity—and propose ways to improve the usefulness of existing surveys to analyze conflict processes at the micro-level. Violent conflict, households, survey methods, questionnaire design.